Higher education in Thailand : critical perspectives - Sinlarat, Paitoon (Texbook and Academic Document Center, Faculty of Education, Chulalongkorn University, 2020)
This book entitled “Higher Education in Thailand: Critical Perspectives” is a collection of academic articles written on various occasions. Some of them are papers presented at international conferences; some were originally in Thai and were later translated into English. I would like to express my sincere gratitude to the editors of the educational journals and the organizing committees of several international conferences in allowing my works to be presented. I personally hope that this book can to a certain extent, offer readers broad and critical perspectives into higher education in Thailand